1985
DOI: 10.1002/bjs.1800720418
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pilonidal disease: A randomized trial with a complete 3-year follow-up

Abstract: Three treatments for chronic pilonidal disease were compared in a randomized trial. Healing without formation of new sinuses occurred equally frequent after excision (E), excision with suture (E + S) and excision with suture under cover with clindamycin (E + S + C). The times of healing were significantly shorter after E + S (median 14 days, n = 29) than after E (64 days, n = 29) and tended to be even shorter after E + S + C (11 days, n = 30). Recurrence rates within 3 years amounted to 13 per cent after E, 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
1
28

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(121 citation statements)
references
References 7 publications
4
88
1
28
Order By: Relevance
“…Outcome of our study in terms of recurrence of the sinus is the same as reported by other studies, namely, three recurrences for the primary closure group against zero recurrence of the Limberg flap group. Fist, a drawback of follow-up of less than 3 years for documenting the recurrence mars the such data of many of the studies since most of the recurrences present within 3 years of the primary procedure [9,10]. Second, most of the published studies have failed to define recurrence and the second occurrence of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Outcome of our study in terms of recurrence of the sinus is the same as reported by other studies, namely, three recurrences for the primary closure group against zero recurrence of the Limberg flap group. Fist, a drawback of follow-up of less than 3 years for documenting the recurrence mars the such data of many of the studies since most of the recurrences present within 3 years of the primary procedure [9,10]. Second, most of the published studies have failed to define recurrence and the second occurrence of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of this method is that all the inflamed tissue is removed and chance of recurrence is minimum. 20 Healing time was defined as complete re-epithelization of the wound.…”
Section: Group Iii: Open/wide Excision and Healing By Secondary Intenmentioning
confidence: 99%
“…20 Despite this there is a role for wide excision in those with extensive chronic disease and following failed primary closure surgical technique. A modification of the standard excision is 'marsupialization'.…”
mentioning
confidence: 99%
“…In all patients, primary healing was achieved, a result that is similar to our own experience. Kronborg and colleagues 12 reported the results of a randomized trial of treatment by 1 of 3 methods: excision, excision with suture and excision with suture and antibiotic coverage with clindamycin. Recurrences rates were 13%, 25% and 19%, respectively.…”
Section: Discussionmentioning
confidence: 99%